Proteins comparison through probabilistic optimal structure local alignment - Micale, Giovanni; Pulvirenti, Alfredo; Giugno, Rosalba; Ferro, Alfredo (Frontiers in Genetics, 2014)
Multiple local structure comparison helps to identify common structural motifs or conserved binding sites in 3D structures of distantly related proteins. Since there is not a best way to compare structures and evaluate the alignment, a wide variety of techniques and different similarity scoring scheme have been proposed. Existing algorithms usually compute the best superposition of two structures or solve it as an optimization problem in a simpler setting (i.e. considering contact maps or distance matrices). Here, we present PROPOSAL (PROteins comparison through Probabilistic Optimal Structure local ALignment), a stochastic algorithm based on iterative sampling for multiple local alignment of protein structures. Our method can efficiently find conserved motifs across a set of protein structures. Only the distances between all pairs of residues in the structures are computed. To evaluate the accuracy and the effectiveness of PROPOSAL we tested it on different families of protein structures and known motifs. PROPOSAL is available as a Java 2D standalone application or a command line program at http://ferrolab.dmi.unict.it/proposal/proposal.html.